Assessment of Electromagnetic-Based Sensing Modalities for Red Palm Weevil Detection in Palm Trees - Mohammed M. Bait-Suwailam; Nassr Al-Nassri; Fahd Al-Khanbashi (Advances in Science, Technology and Engineering Systems Journal, 2022)
In this paper, we investigate the utilization of three effective detection methods to identify potential threats of insects in date palm trees. The detection techniques presented here are the application of infrared radiation, microwave antennas and metamaterials based sensors. Experimental trials using IR radiation took place in a local farm. Moreover, the second sensing system is based on microwave antennas that are designed and numerically simulated at the 2.45 GHz-band. Lastly, the third detection method focuses on the design and development of low-power microwave sensor based on metamaterials concept. Based on the processed and analyzed results, the aforementioned sensing techniques are able to predict existence of red palm weevils within date palms.
Keywords: Date palm; Microwaves; Red palm weevil